Model Pendidikan Keluarga Nabi Ibrahim - Risal Qori Amarullah; Edy (STIT Sirojul Falah Bogor, 2024)
In this modern era, parents feel that parents face enormous challenges in family education. This is related to the rapid flow of globalization and the rapid pace of information and communication technology. The rapid flow of information and communication makes our children need a very, very strong filter. for himself, therefore the family today needs an educational model that is used to rearrange the pattern of education in the family in order to face the great challenges of this globalization. This research contains types of library research; the approach used in this research is an interpretive approach; the methods that will be used in this research are thematic methods, namely collecting verses of the Qur'an, which have the intent to discuss the family of the Prophet Ibrahim. Prophet Ibrahim's family education model employs two methods for educating his son: educational materials and educational methods. Educational materials include monotheism education and moral education, and Prophet Ibrahim always prayed for his son to become a pious child, as he does in Surah As-Shaffat verse 1 .